Career Coaching 5.0: A Strategic Career Guidance Model for Enhancing University Students’ Employability Skills in the Era of Disruption - Rahmatullah; St. Hajrah Syam (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Rapid transformations in the global labor market driven by digitalization, automation, and artificial intelligence require higher education graduates to possess adaptive employability skills that extend beyond technical competencies alone. However, conventional career guidance services in higher education have not yet been fully effective in developing these competencies holistically. This study aims to examine the implementation of Career Coaching 5.0 as an innovative career guidance model that integrates humanistic approaches with digital technology to enhance students’ employability skills. This research adopted a qualitative exploratory case study design conducted over six months at Universitas Islam Ahmad Dahlan, Indonesia. Data were collected through in-depth interviews, participatory observations, and document analysis involving undergraduate students, academic advisors, and professional career coaches. Data were analyzed using thematic analysis through open, axial, and selective coding stages. The findings reveal four main themes: increased students’ career self-awareness, strengthened core soft skills, the transformation of coaches’ roles into reflective facilitators, and the integration of digital approaches through online learning platforms, digital career assessment applications, and virtual communication media, which enhanced service flexibility and accessibility. This study contributes by proposing and empirically examining a Career Coaching 5.0 strategic model that effectively develops students’ adaptive career competencies. These findings imply the need for higher education policies that support the development of coaching-based, human-centered, and digitally integrated career services. Keywords: career coaching 5.0, career guidance, digital transformation, employability skills, higher education